2019
DOI: 10.1111/jcmm.14840
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of proteolipid protein 2 increases ER stress‐induced apoptosis and autophagy in glioblastoma

Abstract: Proteolipid protein 2 (PLP2) is an integral ion channel membrane protein of the endoplasmic reticulum. The protein has been shown to be highly expressed in many cancer types, but its importance in glioma progression is poorly understood. Using publicly available datasets (Rembrandt, TCGA and CGGA), we found that the expression of PLP2 was significantly higher in high‐grade gliomas than in low‐grade gliomas. We confirmed these results at the protein level through IHC staining of high‐grade (n = 56) and low‐grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…5a, b and Supplementary Table 1 ). In contrast, treatment with CH223191 robustly altered the GBMO-30 transcriptome, resulting in 771 DEGs, including several prognostically important chemokines and interleukins in GBM, such as CCL20 32 and IL1B. Network analysis demonstrated the central role of AHR in DEGs ( Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…5a, b and Supplementary Table 1 ). In contrast, treatment with CH223191 robustly altered the GBMO-30 transcriptome, resulting in 771 DEGs, including several prognostically important chemokines and interleukins in GBM, such as CCL20 32 and IL1B. Network analysis demonstrated the central role of AHR in DEGs ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Importantly, we determined that ten of the 41 genes were downregulated following AHR inhibition in GBMO-30 and significantly associated with survival supporting a role of inactivation of AHR on potential genes that drive mortality in GBM. These include PLP2 , a gene involved in autophagy and ER stress in GBM 32 ; SGMS2, which is associated with aggressive breast cancer 33 ; MT1H, which is a tumor suppressor in liver cancer 34 ; and SERPINE1 , which is associated with several cancers 35 ( Fig. 7b- e ).…”
Section: Resultsmentioning
confidence: 99%
“…Proteolipid protein 2 (PLP2) is an integral ion channel membrane protein of the endoplasmic reticulum (ER) [10]. While the exact function of PLP2 under normal conditions is not known, the study of the protein has revealed several features in ER.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it is an integral membrane protein that localizes to the ER. Secondly, PLP2-knockout mice display increased ER stress in neurons under hypoxia, which leads to apoptotic cell death [11]; downregulation of PLP2 increased ER stress-induced apoptosis and reduced tumor cell survival in vitro [10]. In contrast, proteasome inhibition (bortezomib) induces ER stress due to accumulation of misfolded and unfolded proteins in the ER, which leads to myeloma cell death [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation